2019
DOI: 10.15296/ijwhr.2020.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interval Training on Oxidative Stress Indices Among Women in Preterm Labor Underwent Coronary Artery Bypass Graft

Abstract: Objectives: Oxidative stress indices are one of the factors that cause and exacerbate cardiovascular diseases in postpartum women, which can be changed with interval training. Therefore, the current study aimed at investigating the effect of interval training on oxidative stress indices among women in preterm labor undergoing the coronary artery bypass graft (CABG). Materials and Methods: This randomized clinical trial was conducted on 21 participants (the sample size was determined based on a similar study) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In an RCT on animal models performed by Apaijai, it was concluded that despite previous evidence of cardio protective effects of metformin, this drug has a very limited effect on HRV indices [20,[34][35][36]. Paolisso's study reflected that insulin treatment in a patient with insulin resistance cannot improve autonomic system function [21,[37][38][39]. In another study in the United States, it was found that the blood level of insulin was inversely proportional to HF and LF parameters, and in fact, people with high levels of insulin in their blood have a lower HRV.…”
Section: Resultsmentioning
confidence: 99%
“…In an RCT on animal models performed by Apaijai, it was concluded that despite previous evidence of cardio protective effects of metformin, this drug has a very limited effect on HRV indices [20,[34][35][36]. Paolisso's study reflected that insulin treatment in a patient with insulin resistance cannot improve autonomic system function [21,[37][38][39]. In another study in the United States, it was found that the blood level of insulin was inversely proportional to HF and LF parameters, and in fact, people with high levels of insulin in their blood have a lower HRV.…”
Section: Resultsmentioning
confidence: 99%
“…We think it is probably because first, we choose patients with the worse condition for dualchamber pacing than a single chamber. In addition, several potential settings should be taken into accounts such as dual-chamber pacing with short atrioventricular (AV) delay, ventricular pacing with a high base rate, and no programming of features that promote intrinsic ventricular rhythm [27][28][29]. Therefore, these results indicate that implanting a dual-chamber pacemaker needs a more precise basal setting to prevent high pacing dependency.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…[ 6 ] Research indicates that the possibility of neurodevelopmental and behavioral disorders is higher in premature-born children and adults. [ 7 8 ] For example, Moore et al .’s[ 9 ] study on the developmental status of 1,031 three-year-old children with less than 27 weeks of gestational age showed the incidence of moderate-to-severe developmental disorders in 25% of these children. A similar study in Sweden found that 18.8% of preterm infants had cognitive disorders at six years of age.…”
Section: Introductionmentioning
confidence: 99%